Keanekaragaman Tumbuhan Lumut Di Kawasan Hutan Sekipan Desa Kalisoro Tawangmangu Kabupaten Karanganyar Provinsi Jawa Tengah - Setyawati, Rahmadani Ika, Efri Roziaty, S.Si., M.Si (2017)
This research is about Diversity of Moss Plant in Sekipan Area of Kalisoro Tawangmangu Village of Karanganyar Regency of Central Java Province which was implemented in April 2017. The purpose of this research is to know the level of diversity of moss plants in Sekipan forest area. The location of the research is determined by purposive sampling with explorative method consisting of 5 stations. The results of the study found 17 species with 7 orders (including: Marchantiles, Jungermaniales,Bryales, Anthocerotales, Hypnales, Dricanales, Pottiales) and 10 families (including : Marchantiaceae, Geocalycaceae, Polyricaeae, Racopilaceae, Bryaceae, Rhizogoniaceae, Anthocerataceae, Hypnaceae, Leucobryceae and Octoblepharaceae ). The results of the diversity index (H ') is 1.1163. It can be said that the diversity of moss weeds in the forest area of Sekipan tawangmangu is the medium category.